Clinical features and treatment of COVID‐19 patients in northeast Chongqing. Issue 7 (1st April 2020) - Wan, Suxin; Xiang, Yi; Fang, Wei; Zheng, Yu; Li, Boqun; Hu, Yanjun; Lang, Chunhui; Huang, Daoqiu; Sun, Qiuyan; Xiong, Yan; Huang, Xia; Lv, Jinglong; et al.
Abstract: The outbreak of the novel coronavirus in China (SARS‐CoV‐2) that began in December 2019 presents a significant and urgent threat to global health. This study was conducted to provide the international community with a deeper understanding of this new infectious disease. Epidemiological, clinical features, laboratory findings, radiological characteristics, treatment, and clinical outcomes of 135 patients in northeast Chongqing were collected and analyzed in this study. A total of 135 hospitalized patients with COVID‐19 were enrolled. The median age was 47 years (interquartile range, 36‐55), and there was no significant gender difference (53.3% men). The majority of patients had contact with people from the Wuhan area. Forty‐three (31.9%) patients had underlying disease, primarily hypertension (13 [9.6%]), diabetes (12 [8.9%]), cardiovascular disease (7 [5.2%]), and malignancy (4 [3.0%]). Common symptoms included fever (120 [88.9%]), cough (102 [76.5%]), and fatigue (44 [32.5%]). Chest computed tomography scans showed bilateral patchy shadows or ground glass opacity in the lungs of all the patients. All patients received antiviral therapy (135 [100%]) (Kaletra and interferon were both used), antibacterial therapy (59 [43.7%]), and corticosteroids (36 [26.7%]). In addition, many patients received traditional Chinese medicine (TCM) (124 [91.8%]). It is suggested that patients should receive Kaletra early and should be treated by a combination of Western and Chinese medicines. Compared to the mild cases, the severe ones had lower lymphocyte counts and higher plasma levels of Pt, APTT, d‐dimer, lactate dehydrogenase, PCT, ALB, C‐reactive protein, and aspartate aminotransferase. This study demonstrates the clinic features and therapies of 135 COVID‐19 patients. Kaletra and TCM played an important role in the treatment of the viral pneumonia. Further studies are required to explore the role of Kaletra and TCM in the treatment of COVID‐19. Research Highlights: 83.7% of the patients had contact history in Wuhan or had been to Wuhan or had contact with people from Wuhan. Common symptoms included fever, cough, and fatigue. Other symptoms include myalgia, fatigue, dyspnea, anorexia, etc. Common complications of the patients include acute respiratory distress syndrome, acute cardiac injury, acute kidney injury, secondary infection and shock. ICU patients were more likely to have these complications than non‐ICU patients. Compared with non‐ICU patients, ICU patients had lower lymphocyte count, and higher plasma levels of the Pt, APTT, D‐dimer, LDH, PCT, ALB, CRP, AST. All patients received antiviral therapy (kaletra or interferon), antibacterial therapy and corticosteroid and many received traditional chinese medicine. It was suggested that patients should use kaletra early.